2009
DOI: 10.3354/meps07949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in number, identity and abundance of habitat-forming species on assemblages of rocky seashores

Abstract: Understanding the relationship between variation in biodiversity and the alteration of ecosystem processes and stability has become a central ecological issue during the last decade. A large number of experimental and theoretical studies have focused on the effects of changes in species richness and identity, while the role of variation in species abundance has received less attention in biodiversity experiments. By using an experimental design that effectively separates the effects of species richness and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 91 publications
0
41
1
1
Order By: Relevance
“…O 'Connor & Crowe (2005) found that the identity of species of grazers was more important than their number in determining patterns of algal productivity, after controlling for changes in density. Similarly, Maggi et al (2009) performed a study on the effects of changes in composition of intertidal assemblages using an experimental design to separate the effects of species richness and identity, while controlling for variation in species abundance. Their results showed significant effects of changes in number and identity of habitat-forming species on other organisms, even though the magnitude and direction of these effects were determined by the abundance of manipulated species.…”
Section: Discussionmentioning
confidence: 99%
“…O 'Connor & Crowe (2005) found that the identity of species of grazers was more important than their number in determining patterns of algal productivity, after controlling for changes in density. Similarly, Maggi et al (2009) performed a study on the effects of changes in composition of intertidal assemblages using an experimental design to separate the effects of species richness and identity, while controlling for variation in species abundance. Their results showed significant effects of changes in number and identity of habitat-forming species on other organisms, even though the magnitude and direction of these effects were determined by the abundance of manipulated species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our prediction, no effects of barnacle cover emerged on total MPB biomass (or maximum photosynthetic efficiency) at the lower latitude in spite of the higher thermal and desiccation stress characterizing southern sites in comparison to northern ones. Geographic variation in barnacle cover might have played a role in driving changes in the intensity of positive interactions (Irving & Bertness 2009, Maggi et al 2009). However, although mean barnacle cover was smaller in the South than in the North (see Table S1), significant differences among treatment levels at northern sites suggested that this was not the cause of the lack of effects at southern ones.…”
Section: Discussionmentioning
confidence: 99%
“…By creating habitats and modifying the environment, foundation species exert positive effects on a wide range of organisms (Bruno & Bertness 2001, Altieri & van de Koppel 2014 and references therein), thus setting the stage for an ecological network of interactions (Kéfi et al 2012). Relatively recent studies demonstrated that traits of the benefactor species, such as its density, can modify the strength of facilitation in aquatic systems (Irving & Bertness 2009, Maggi et al 2009). Our results showed that barnacles can facilitate MPB and littorinids through density-dependent positive effects resulting from the provision of suitable habitat and likely by ameliorating abiotic conditions on adjacent rock surfaces.…”
Section: Climatic Conditions Density Dependence Local Stressors Andmentioning
confidence: 99%
See 1 more Smart Citation
“…These included articulated corallines (mostly Corallina elongata), coarsely branched algae, and non-manipulated filamentous algae (these filamentous algae appeared at later stages of succession, mainly as epiphytes of other organisms, even though they were characterized by fast growth rates). Two other species, the brown canopy-forming alga Cystoseira compressa and the mussel Mytilus galloprovincialis, were included in the univariate analyses even if they did not attain high cover on the experimental plates, because they are important habitat formers at the study site (Maggi et al 2009). Univariate analyses extended the mixed-effect model used for the multivariate case by including time as a predictor, so that the estimates of linear and quadratic rates of change in abundance of organisms (i.e., the slope of temporal trajectories of abundances) were compared among the different experimental conditions (i.e., at increasing levels of richness and abundance in factorial combinations).…”
Section: Sampling and Statistical Analysismentioning
confidence: 99%